Corpus Vasorum Antiquorum, Fascicule 10: Athenian Red-Figure Column and Volute Kraters - Despoina Tsiafakis (Getty Publications, 2019)
This expansive catalogue of ancient Greek painted pottery brings an important series into the digital age with a new open-access format. Cataloging some hundred thousand examples of ancient Greek painted pottery held in collections around the world, the authoritative Corpus Vasorum Antiquorum (Corpus of Ancient Vases) is the oldest research project of the Union Acad